2012
DOI: 10.1159/000342824
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Neuropsychiatric Symptoms in Young-Onset Compared to Late-Onset Alzheimer’s Disease – Part 1: Findings of the Two-Year Longitudinal NeedYD-Study

Abstract: Background/Aims: Knowledge about neuropsychiatric symptoms in young-onset Alzheimer’s disease (YO-AD) is scarce, but essential to establish a prognosis and plan care for YO-AD patients. The aim of this study is to assess frequency parameters of neuropsychiatric symptoms in YO-AD over 2 years and investigate whether there are differences compared with late-onset Alzheimer’s disease (LO-AD). Methods: 98 YO-AD and 123 LO-AD patients and caregivers from two prospective cohort studies were included and assessed eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 55 publications
4
64
1
Order By: Relevance
“…Moreover, they found fewer delusions and hallucinations as well as less agitation, disinhibition, and aberrant motor behavior in YO-AD than in LO-AD. van Vliet et al (2012) also found lower incidence and prevalence rates of NPS in community-dwelling people with YO-AD than in those with LO-AD. In addition, Mushtaq et al (2016) found higher levels of delusions, agitation, anxiety, disinhibition and nighttime behavioral disturbances in community-dwelling people with LO-AD than in those with YO-AD.…”
Section: Introductionmentioning
confidence: 68%
“…Moreover, they found fewer delusions and hallucinations as well as less agitation, disinhibition, and aberrant motor behavior in YO-AD than in LO-AD. van Vliet et al (2012) also found lower incidence and prevalence rates of NPS in community-dwelling people with YO-AD than in those with LO-AD. In addition, Mushtaq et al (2016) found higher levels of delusions, agitation, anxiety, disinhibition and nighttime behavioral disturbances in community-dwelling people with LO-AD than in those with YO-AD.…”
Section: Introductionmentioning
confidence: 68%
“…The development of YOD and receiving the dementia diagnosis are reasonably followed by anxiety, turmoil, depression (Haugen, 2012; Johannessen & Möller, 2013), reduced quality of life and increased problems in everyday life in relation to work, friends and family (Spreadbury & Kipps, 2017). Behaviour will change, and behavioural changes are more frequent in YOD than in people with late-onset dementia (LOD; van Vliet et al, 2012). Usually, people with YOD are diagnosed at a later stage of the disease compared to people with LOD (Harvey et al, 2003; Koedam et al, 2008; Luscombe et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies found QOL in community-dwelling people with YOD to be associated with depressive symptoms [39, 40]. A Dutch study found a generally low prevalence of NPS in young-onset AD compared to late-onset AD during a 2-year follow-up [41]. In nursing home residents, Appelhof et al [42] found a significant association between NPS and psychotropic drug use and QOL.…”
Section: Introductionmentioning
confidence: 99%